2020
DOI: 10.1186/s13046-020-01581-3
|View full text |Cite|
|
Sign up to set email alerts
|

Sur-X, a novel peptide, kills colorectal cancer cells by targeting survivin-XIAP complex

Abstract: Background Survivin and XIAP are two important members of the inhibitor of apoptosis protein family and have been considered as potential targets for cancer treatment due to their overexpression in large variety of cancers including colorectal cancer. It has been reported that survivin and XIAP can synergistically inhibit apoptosis by forming survivin-XIAP complex. In this study, we aimed to design a peptide that targets the survivin-XIAP complex and elucidate its anticancer mechanisms in color… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…This complex promotes XIAP stability against ubiquitination/proteasomal destruction and synergistically inhibits caspase-9 activation (Dohi et al 2004). Accumulating evidence has shown that dual inhibition of survivin and XIAP effectively inhibits cancer proliferation and migration and induces apoptosis (Cao et al 2004;Yi et al 2015;Werner et al 2017;Li et al 2018;Chang et al 2020;Fang et al 2020). Therefore, the inhibition of ET-2 could be an effective strategy to inhibit LUAD progression through the dual inhibition of XIAP-survivin.…”
Section: Discussionmentioning
confidence: 99%
“…This complex promotes XIAP stability against ubiquitination/proteasomal destruction and synergistically inhibits caspase-9 activation (Dohi et al 2004). Accumulating evidence has shown that dual inhibition of survivin and XIAP effectively inhibits cancer proliferation and migration and induces apoptosis (Cao et al 2004;Yi et al 2015;Werner et al 2017;Li et al 2018;Chang et al 2020;Fang et al 2020). Therefore, the inhibition of ET-2 could be an effective strategy to inhibit LUAD progression through the dual inhibition of XIAP-survivin.…”
Section: Discussionmentioning
confidence: 99%
“…Induced-H19 ( Figure 3 B) enhances activation of NF-κb signaling promoting expression of pivotal oncogenic genes such as Blc-2 and XIAP—which are upregulated in several human gliomas and to protect from apoptosis cellular [ 100 , 101 ]. As is the case for BCL-2 or XIAP, H19 increases Cyclin D1 expression, which mediates cycle cellular transition leading to a higher proliferative ratio and preventing malignant cells from being retained in the G2/M phase [ 102 ]. As a consequence of enhancing expression of those oncogenic genes, TMZ fails to induce cell cycle arrest and apoptosis resulting in acquisition of resistance against this drug [ 103 ].…”
Section: Lncrna H19 Impairs Chemo and Radiotherapy In Gliomamentioning
confidence: 99%
“…Therefore, the design of peptides that target the BIRC5/XIAP interface is important in the context of activating anti-tumor mechanisms in cells. Peptide Sur-X, with the sequence derived from the XIAP-binding region (K15-M38) of survivin and the cell-penetrating sequence from HIV Tat protein added to its N-terminal, was shown to destabilize the BIRC5/XIAP complex and induced growth inhibition and necroptosis in HCT116, HCT15, RKO, and HT29 cells and also had a pro-apoptotic effect in vivo in mouse xenograft models [ 121 ].…”
Section: Targeting Clinically Significant Ppis With Interfacial Peptidesmentioning
confidence: 99%